Effect of pursed-lip breathing and forward trunk lean positions on regional chest wall volume and ventilatory pattern in older adults: An observational study. Issue 4 (28th January 2022) - Ubolnuar, Nutsupa; Tantisuwat, Anong; Mathiyakom, Witaya; Thaveeratitham, Premtip; Kruapanich, Chathipat
Abstract : Abstract: Pursed-lip breathing (PLB) and forward trunk lean posture (FTLP) are commonly used to relieve dyspnea and improve ventilation in a rehabilitation program. However, their effect on chest wall volumes and movements in older adults without chronic obstructive pulmonary disease has never been investigated. This observational study aimed to identify the effect of combined PLB and FTLP on total and regional chest wall volumes, ventilatory pattern, and thoracoabdominal movement using in older adults. It was hypothesized that the combined PLB with FTLP would result in the highest chest wall volumes among the experimental tasks. Twenty older adults performed 2 breathing patterns of quiet breathing (QB) and PLB during a seated upright (UP) position and FTLP. An optoelectronic plethysmography system was used to capture the chest wall movements during the 4 experimental tasks. Tidal volume (VT ) was separated into pulmonary ribcage, abdominal ribcage, and abdomen volume. The changes in anterior–posterior (AP) and medial–lateral (ML) chest wall diameters at 3 levels were measured and used to identify chest wall mechanics to improve chest wall volumes. The PLB significantly improved ventilation and chest wall volumes than the QB ( P < .05). VT of pulmonary ribcage, VT of abdominal ribcage, and VT were significantly higher during the PLB + UP ( P < .05) and during the PLB + FTLP ( P < .01) as compared to those of QB performed in similar body positions. However, there was no significant in total and regional lung volumes between the PLB + UP and the PLB + FTLP. The AP diameter changes at the angle of Louis and xiphoid levels were greater during the PLB + UP than the QB + UP and the QB + FTLP ( P < .01). The AP diameter changes at the umbilical level and the ML diameter changes at the xiphoid level were significantly larger during the PLB + FTLP than the QB + FTLP and the QB + UP ( P < .05). The ML diameter changes at the umbilical level were significantly greater during the PLB + FTLP than the QB + UP ( P < .05). However, no significant difference in the relative regional chest wall volumes and phase angle among the experimental tasks ( P > .05). In conclusion, a combined PLB performed in an FTLP or UP sitting could be used as a strategy to improve chest wall volumes and ventilation in older adults.